On the phraseology of the linking adverbial besides. Issue 40 (July 2019) - Kim, Sugene; Yeates, Robert
Abstract: This paper examines the phraseology of the linking adverbial besides to unravel why, unlike similar-meaning transitions such as in addition, it sounds unnatural in some contexts (e.g., His efforts finally paid off. He successfully defended his dissertation; besides, he got a job offer ). A total of 217 instances from four academic (sections of) written English corpora—the Michigan Corpus of Upper-level Student Papers, the British Academic Written English corpus, the British National Corpus, and the Corpus of Contemporary American English—and 45 English dictionaries and grammar reference materials were analyzed to identify its pragmalinguistic features within discourse. The results suggest that while most reference materials define the usage of besides in relation to the nature of the element that follows, no consistent pattern can be discerned across those elements except that the clause introduced by besides functions exclusively as a supporting argument. In contrast, its natural use is found to be regulated by the nature of the preceding statement to which the besides -clause lends support: "Negativity" is encoded syntactically, semantically, or inferentially, entailing argumentative moves within a discourse unit. Pedagogical implications are discussed in light of the findings.